Analisis Stabilitas Keamanan Bendungan Bili-Bili - As'ad, Mohammad Bagus Wiratama; Suripin, Suripin; Wulandari, Dyah Ari (MEDIA KOMUNIKASI TEKNIK SIPIL, 2025)
The Bili-Bili Dam located in Gowa Regency, South Sulawesi Province, is a rockfill dam with a central core, featuring a total storage capacity of 375 million m³ and sediment storage capacity of 29 million m³. Due to its high risk of structural failure, Bili-Bili Dam is classified as Class IV (Extreme). Recent developments have shown a decline in dam body stability due to seepage issues. If left unaddressed, this could trigger piping or even structural failure, posing a threat to the sustainability of the reservoir's functions. The objective of this study is to evaluate the safety factor (SF) of the main dam, right wing dam, and left wing dam as an integrated structural system of Bili-Bili Dam. The approach combines both qualitative and quantitative methods, including engineering geological assessments and Geostudio SEEP/W to analyze seepage rates and SLOPE/W to evaluate landslide potential. The analysis results indicate that seepage discharge remains within acceptable limits, and the dam’s stability under Operating Basis Earthquake (OBE) conditions is considered safe. However, under Maximum Design Earthquake (MDE) conditions, the slope safety factor does not meet the minimum standard required by SNI 8064:2016. Therefore, remedial actions such as reinforcement or retrofitting of the dam body are necessary.